GOALS AND TASKS OF TEACHING LOGICAL PROBLEMS IN PRIMARY CLASS MATHEMATICS COURSE - Turdali Sultanov; Sabina Turginbayeva (Western European Studies, 2024)
This article is about educating elementary school students using the goals and tasks of teaching logical problems in the elementary mathematics course
Keywords: Problem; logical problem; goal; task